Three-dimensional surface printing method for interconnecting electrodes on opposite sides of substrates - Md. Khalilur Rahman (Nature Portfolio, 2020)
Abstract As the application of the direct printing method becomes diversified, printing on substrates with non-flat surfaces is increasingly required. However, printing on three-dimensional surfaces suffers from a number of difficulties, which include ink flow due to gravity, and the connection of print lines over sharp edges. This study presents an effective way to print a fine pattern (~ 30 μm) on three different faces with sharp edge boundaries. The method uses a deflectable and stretchable jet stream of conductive ink, which is produced by near-field electrospinning (NFES) technique. Due to added polymer in the ink, the jet stream from the nozzle is less likely to be disconnected, even when it is deposited over sharp edges of objects. As a practical industrial application, we demonstrate that the method can be effectively used for recent display applications, which require the connection of electrical signal and power on both sides of the glass. When the total length of printed lines along the ‘Π’ shaped glass surfaces was 1.2 mm, we could achieve the average resistance of 0.84 Ω.